Impact of NRAS Mutations on the Diagnosis of Follicular Neoplasm of the Thyroid. (31st August 2014) - Bae, Ja-Seong; Choi, Seung Kyu; Jeon, Sora; Kim, Yourha; Lee, Sohee; Lee, Youn Soo; Jung, Chan Kwon
Abstract : Background . Most patients with a preoperative diagnosis of thyroid follicular neoplasm (FN) undergo diagnostic surgery to determine whether the nodule is benign or malignant. Point mutations at NRAS codon 61 are the most common mutations observed in FN. However, the clinical significance of NRAS mutation remains unclear. Methods . From 2012 to 2013, 123 consecutive patients undergoing thyroidectomy for FN were evaluated prospectively. Molecular analyses for NRAS codon 61 were performed with pyrosequencing. Results . The overall malignancy rate in FN was 48.8% (60/123). Of 123 FNs, 33 (26.8%) were positive for the NRAS mutation. The sensitivity, specificity, positive predictive value, and negative predictive value of a NRAS mutation-positive FN specimen to predict malignancy were 37%, 83%, 67%, and 58%, respectively. Patients with a NRAS -positive FN had a higher malignancy rate in additional thyroid nodules beyond the FN than patients with a NRAS-negative FN. The overall malignancy rate of patients with a NRAS-positive FN was significantly higher than that of patients with a NRAS-negative FN (79% versus 52%; P = 0.008). Conclusions . Determining NRAS mutation status in FN helps to improve the accuracy of thyroid cancer diagnosis and to predict cancer risk in accompanying thyroid nodules.